2000
DOI: 10.1034/j.1399-3003.2000.16f22.x
|View full text |Cite
|
Sign up to set email alerts
|

Absence of bacterial colonization of the airways after therapeutic rigid bronchoscopy without stenting

Abstract: Absence of bacterial colonization of the airways after therapeutic rigid bronchoscopy without stenting. M. Noppen, D. Pie Ârard, M. Meysman, R.V. Herreweghe, W. Vincken. #ERS Journals Ltd 2000. ABSTRACT: Following airway stenting, bacterial colonization of the airways with potentially pathogenic micro-organisms occurs within 4 weeks after treatment in the majority of patients. The objective of this study was to prospectively investigate whether nonstenting therapeutic rigid bronchoscopy (using laser, cryothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…NOPPEN et al [27] reported an 80% incidence of bacterial colonisation (most frequently Staphylococcus aureus) after placement of silicone stents in nontransplant patients without prior colonisation, while bacterial airway colonisation decreased from 45% to 25% following therapeutic rigid bronchoscopy without stent placement [28]. BURNS et al [21] studied colonisation in lung transplant patients with SEMS and demonstrated that 56% of BAL specimens were positive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NOPPEN et al [27] reported an 80% incidence of bacterial colonisation (most frequently Staphylococcus aureus) after placement of silicone stents in nontransplant patients without prior colonisation, while bacterial airway colonisation decreased from 45% to 25% following therapeutic rigid bronchoscopy without stent placement [28]. BURNS et al [21] studied colonisation in lung transplant patients with SEMS and demonstrated that 56% of BAL specimens were positive.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective cohort study was performed at Hanover Medical School (Hanover, Germany) between January 1, 1998 and February 28,2008. Inclusion criteria were patients undergoing lung transplantation and technically successful insertion of SEMS with follow-up of at least 7 days.…”
Section: Methodsmentioning
confidence: 99%
“…That analysis demonstrated that there was no signifi cant bacterial colonization as assessed by protected-specimen brush cultures. 11 To our knowledge, however, no studies before ours have compared the incidence rates of infections in patients undergoing therapeutic bronchoscopy with ablative techniques alone, with ablative techniques plus stenting. To our knowledge, our study is also the fi rst to use incidence rates and survival analysis methods to quantify the risk difference between patients with stents and those without stents for the outcome of respiratory tract infections.…”
Section: Restenosis Due To Tumor Overgrowthmentioning
confidence: 91%
“…Mixed reports from previous studies suggest limited association between bronchoscopy and subsequent colonization of the lower respiratory tract. 19 Our study demonstrates in control patients who have undergone bronchoscopy alone, without stent insertion only 25% of patients were colonized. This is similar to that reported in the adult population suggesting the effect of bronchoscopy alone to be minimal in colonizing distal airways.…”
Section: Discussionmentioning
confidence: 61%
“…It is feasible that the mechanical introduction of the bronchoscope into the airway may potentially facilitate transfer of microorganisms from upper respiratory tract into the distal airways. Mixed reports from previous studies suggest limited association between bronchoscopy and subsequent colonization of the lower respiratory tract . Our study demonstrates in control patients who have undergone bronchoscopy alone, without stent insertion only 25% of patients were colonized.…”
Section: Discussionmentioning
confidence: 69%